The Birkman method : your personality at work - Birkman Fink, Sharon, 1950- (Jossey-Bass, A Wiley Brand, 2013)
By explaining how the various factors revealed by The Birkman Method personality assessment fit together and work off each other, this text becomes your guide to a deeper self-awareness that can help you attain more inspiring leadership, better team harmony, and higher goals for you personally and throughout any organization.